ENHANCING LEARNING THROUGH DIGITAL TECHNOLOGIES: A RESEARCH PERSPECTIVE - Abdul Rehman Khan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The research paper critically explores the multifaceted landscape of digital education to understand its impact on the learning process. This study delves into the various digital technologies employed in educational settings, examining their effectiveness and challenges. The abstract begins by acknowledging the transformative potential of digital technologies in education and highlights the importance of adopting a research-oriented perspective. The paper investigates the diverse array of digital tools, platforms, and methodologies utilized to enhance the learning experience. It scrutinizes the implications of digital education on pedagogical approaches, student engagement, and overall educational outcomes. Furthermore, the research examines the challenges and limitations associated with the integration of digital technologies in learning environments. Issues such as access, equity, and the potential digital divide are explored, providing a comprehensive understanding of the broader implications of technology in education. The abstract concludes by emphasizing the significance of ongoing research in shaping the future of digital education. By presenting a research-focused perspective, the paper aims to contribute valuable insights to the academic community, policymakers, and educators, fostering a deeper understanding of the opportunities and challenges in leveraging digital technologies for enhanced learning experiences.